Effect of Substituting Polyether Ionophore Anticoccidial Drugs With 1, 8‐Cineole for the Control of Eimeria Infections in Broilers - Jing Sun; Wanjun Bao; Ye Han; Rongfei Zhang; Zhijiang Zhou (Veterinary Medicine and Science)
ABSTRACT Background Coccidiosis is an important parasitic disease of broiler chickens. Drug resistance to the polyether polyether Ionophore anticoccidial drugs  (PACDs) caused by long‐term use has emerged as a significant problem in commercial broiler chicken production. Objectives This study explored the feasibility of 1,8‐cineole (CIN) in replacing PACD with broiler feeding experiments and intestinal microecological experiments. Methods This experiment selected 21‐day‐old Lingnan yellow (LNY) broilers and randomly divided them into 8 groups, with 30 chickens in each group. They were uniformly fed with full feed during the breeding period. The experimental groups were as follows: (i) three broiler groups that were fed a PACD supplementation (G1: Salinomycin Premix [SAP] 60 mg/kg; G2: Monensin Premix [MOP] 100 mg/kg and G3: Maduramicin Premix [MAP] 5 mg/kg), (ii) three broiler groups that were administered different CIN dosages (G4: CIN‐L 100 mg/kg, G5: CIN‐M 150 mg/kg and G6: CIN‐H 250 mg/kg) and (iii) two control broiler groups (G7: infected control group and G8: healthy control group). On the 23rd day, all groups were infected with coccidian cysts, except the G8 group which was used as a blank control. After 2 weeks of continuous feeding, the growth performance changes of broilers were analysed, and the intestinal lesions of eight groups of broilers were analysed after slaughter. Results Compared with PACD treatment, the average daily feed intake (ADFI) of the three CIN‐treated groups increased by 13%, whereas the feed conversion ratio (FCR) reduced by 28%. FCR value for the high‐dose CIN treatment was 2.04, 34% decline which compared with control group infected with spore oocysts. The anticoccidial index (ACI) of all PACD treatments was less than 120, whereas the ACI of the middle‐ and high‐dose CIN treatments was higher than 180. In comparison to the Eimeria‐infected control group, the diversity and total number of the microbiota in the CIN treatments increased significantly. Moreover, CIN treatment favoured the proliferation of intestinal probiotics, especially Lactobacillus sp. Conclusions CIN could have an inhibitory effect on parasite development as suggested in the gene function annotation of the intestinal microbiota. These results demonstrate that CIN may be a feasible natural alternative to anticoccidiosis drugs. So it was important to take precautions against and control coccidiosis in poultry production which has a lesser risk of creating resistance to substitutive PACDs.